Normalization of Student Cohabitation and Its Implications for Social Functioning: An Ecological Social Work Perspective from Jember, Indonesia - Akhmad Munif Mubarok; Aura Pamungkas; Khotibul Umam; Kusuma Wulandari (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2025)
Student cohabitation has become an increasingly visible phenomenon in university towns; however, it is often normatively framed as moral deviation or individual misconduct. Limited attention has been given to understanding cohabitation as a social–ecological process that shapes students’ social functioning, particularly from a social work perspective in non-Western contexts. This study aims to analyze the normalization of student cohabitation and its implications for social functioning through an ecological social work lens. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews, non-participant observation, and document analysis involving students engaged in cohabitation, boarding house managers, and community actors in Sumbersari Village, Jember Regency, Indonesia. The data were analyzed thematically to capture the interactions among individual experiences, relational dynamics, and environmental structures. The findings indicate that student cohabitation is normalized through emotional closeness, practical considerations, and permissive housing environments. Students develop adaptive attitudes such as indifference to social judgment, personal rationalization, and selective disclosure of their relationships. Regarding social functioning, cohabitation produces ambivalent outcomes. On one hand, it strengthens emotional support and academic motivation; on the other, it may limit broader social engagement and increase emotional dependency, particularly when relational disruptions occur. This study demonstrates that student cohabitation should be understood as a social–ecological phenomenon rather than a purely individual choice. Its main contribution lies in advancing social work scholarship by positioning cohabitation as an issue of social functioning within a person-in-environment framework. The findings highlight the importance of preventive, community-based social work interventions in higher education settings, particularly those aimed at promoting healthy relationship literacy, emotional autonomy, and sustainable social support systems for students. Keywords: student cohabitation, social functioning, ecological systems theory, normalization, social work Kohabitasi mahasiswa merupakan fenomena yang semakin terlihat di kawasan pendidikan tinggi, namun masih kerap dipahami secara normatif sebagai penyimpangan moral atau persoalan individual. Kajian yang menempatkan kohabitasi sebagai proses sosial-ekologis yang memengaruhi keberfungsian sosial mahasiswa, khususnya dari perspektif pekerjaan sosial di konteks non-Barat, masih sangat terbatas. Penelitian ini bertujuan untuk menganalisis proses normalisasi kohabitasi mahasiswa serta implikasinya terhadap keberfungsian sosial melalui perspektif pekerjaan sosial berbasis ekologi. Penelitian ini menggunakan pendekatan kualitatif dengan desain fenomenologis. Data dikumpulkan melalui wawancara mendalam, observasi non-partisipan, dan studi dokumentasi terhadap mahasiswa pelaku kohabitasi, pengelola kos, serta aktor lingkungan di Kelurahan Sumbersari, Kabupaten Jember. Analisis data dilakukan secara tematik untuk menangkap interaksi antara pengalaman individual, dinamika relasional, dan struktur lingkungan sosial. Hasil penelitian menunjukkan bahwa kohabitasi mahasiswa dinormalisasi melalui kedekatan emosional, pertimbangan praktis, serta lingkungan hunian yang permisif. Mahasiswa mengembangkan sikap adaptif berupa ketidakpedulian terhadap penilaian sosial, rasionalisasi personal, dan keterbukaan selektif dalam mengelola relasi. Dari sisi keberfungsian sosial, kohabitasi menghasilkan dampak yang ambivalen. Di satu sisi, kohabitasi memperkuat dukungan emosional dan motivasi akademik; di sisi lain, praktik ini berpotensi membatasi partisipasi sosial yang lebih luas dan meningkatkan ketergantungan emosional, terutama ketika relasi mengalami gangguan. Penelitian ini menegaskan bahwa kohabitasi mahasiswa perlu dipahami sebagai fenomena sosial-ekologis, bukan sekadar pilihan individual. Kontribusi utama penelitian ini terletak pada penguatan perspektif pekerjaan sosial dengan memposisikan kohabitasi sebagai isu keberfungsian sosial dalam kerangka person-in-environment. Temuan penelitian ini menekankan pentingnya intervensi pekerjaan sosial yang bersifat preventif dan berbasis komunitas di lingkungan perguruan tinggi, khususnya dalam penguatan literasi relasi sehat, kemandirian emosional, dan sistem dukungan sosial mahasiswa yang berkelanjutan. Kata kunci: kohabitasi mahasiswa, keberfungsian sosial, teori sistem ekologi, normalisasi sosial, pekerjaan sosial.